2011
DOI: 10.1080/02601370.2011.627473
|View full text |Cite
|
Sign up to set email alerts
|

Adults who learn: sharing literacy project experience from South-western Nigeria

Abstract: The paper reports the outcome of a funded non-formal, functional adult literacy project embarked upon in the university-based I soya rural development programme area in southwestern Nigeria from 2005-2007. It specifically presents the approaches used in legitimising the literacy project amongst community people; and reports the positive impact of the project on community empowerment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…Finding from research hypothesis two showed that gender does not determine the level of cognitive sustainability of adult learners. This result contradicts the findings of Kolawole, (2011) who argued that gender as prove to be a major determinant of learning among adult learners. An average African woman has so much responsibilities on her shoulder.…”
Section: The Difference Between Language Of Instruction and Cognitive Sustainability Of Adult Learnerscontrasting
confidence: 96%
See 2 more Smart Citations
“…Finding from research hypothesis two showed that gender does not determine the level of cognitive sustainability of adult learners. This result contradicts the findings of Kolawole, (2011) who argued that gender as prove to be a major determinant of learning among adult learners. An average African woman has so much responsibilities on her shoulder.…”
Section: The Difference Between Language Of Instruction and Cognitive Sustainability Of Adult Learnerscontrasting
confidence: 96%
“…Adult learners often see literacy programme as a waste of time given the herculean task ahead of them in terms of family responsibilities and need to survive daily, (Desjardins, & Warnke, 2012;Kolawole, 2011). Kolawole further asserted that adults most especially in the remote part of the country often believed adult literacy programme is synonymous to formal education and are of the opinion that they do not possess the cognitive capability to learn that much or that far; and that their children will enroll in this kind of education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, senility could make people lethargic and might affect their willingness to participate in any adult class instructions. While marital commitment may affect how a married individual would commit to ABEP participation (Kolawole, 2009(Kolawole, , 2011. Different ethnic groups perceive and read meaning to the phenomenon around them differently.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The experiment also had the goal of providing learners with the basic reading and writing skills required for the growth of self-confi dence and self-esteem (Bhola 1984(Bhola , 1990. It was argued that when people are able to express themselves freely and make meaningful and critical judgement of their leaders, and at the same time are able to exploit the resources (both natural and human) at their disposal in a sustainable way, this is development in practice (Kolawole 2011 ).…”
Section: The University Village: An Experimentsmentioning
confidence: 99%